Proceedings of the Thirtieth Annual Symposium on Computational Geometry 2014
DOI: 10.1145/2582112.2582127
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Systolic Inequalities and Decompositions of Triangulated Surfaces

Abstract: How much cutting is needed to simplify the topology of a surface? We provide bounds for several instances of this question, for the minimum length of topologically non-trivial closed curves, pants decompositions, and cut graphs with a given combinatorial map in triangulated combinatorial surfaces (or their dual cross-metric counterpart).Our work builds upon Riemannian systolic inequalities, which bound the minimum length of non-trivial closed curves in terms of the genus and the area of the surface. We first d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In [7] and [12] it was observed that there exists a constant c ′ n such that any simplicial complex X triangulating an essential manifold has at least c ′ n sys(X) n facets (faces of dimension n). Theorem 1.4 provides a condition on a simplical complex that implies the discrete systolic inequality in terms of the vertices, (which in turn, implies the Riemannian version [7] and lower bounds for all the entries of the f -vector which in particular improve significantly the estimate on th constant c ′ n ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [7] and [12] it was observed that there exists a constant c ′ n such that any simplicial complex X triangulating an essential manifold has at least c ′ n sys(X) n facets (faces of dimension n). Theorem 1.4 provides a condition on a simplical complex that implies the discrete systolic inequality in terms of the vertices, (which in turn, implies the Riemannian version [7] and lower bounds for all the entries of the f -vector which in particular improve significantly the estimate on th constant c ′ n ).…”
Section: Introductionmentioning
confidence: 99%
“…In [7] and [12] it was observed that there exists a constant c ′ n such that any simplicial complex X triangulating an essential manifold has at least c ′ n sys(X) n facets (faces of dimension n). Theorem 1.4 provides a condition on a simplical complex that implies the discrete systolic inequality in terms of the vertices, (which in turn, implies the Riemannian version [7] and lower bounds for all the entries of the f -vector which in particular improve significantly the estimate on th constant c ′ n ). Unlike the estimates on the number of n-faces, lower bounds on the number of vertices (in Theorem 1.4) are not easy to derive directly from Riemannian systolic inequalities.Instead our proof adapts the approach of Larry Guth [9] and Panos Papasoglu [16], which is metaphorically referred to as "the Schoen-Yau [18] minimal hypersurface method".…”
Section: Introductionmentioning
confidence: 99%
“…the size of the smallest noncontractible cycles. The question of the systole is a well studied question in the field of geometry of surfaces (see for instance [11; 20; 21] and in particular [9] in the case of deterministic maps).…”
Section: Introductionmentioning
confidence: 99%